Transcatheter closure of patent ductus arteriosus with severe pulmonary arterial hypertension in adults. Issue 4 (5th September 2006) - Yan, C; Zhao, S; Jiang, S; Xu, Z; Huang, L; Zheng, H; Ling, J; Wang, C; Wu, W; Hu, H; Zhang, G; Ye, Z; et al.
Abstract : Background: Surgical closure of patent ductus arteriosus (PDA) with severe pulmonary arterial hypertension in adults carries higher risk than in children. Objectives: To investigate the application of self-expandable occluders for transcatheter closure of PDA associated with severe pulmonary arterial hypertension in adults, and the assessment of immediate and short-term results. Methods: 29 adult patients (6 men, 23 women) underwent attempted transcatheter closure of PDA at a mean (standard deviation (SD)) age of 31.1 (11.4) years (range 18–58 years) and a mean (SD) weight of 54.1 (7.1) kg (range 42–71 kg). On the basis of haemodynamic and clinical data obtained before and after trial occlusion, the final duct occlusion was determined and carried out. Radiographs of the chest, electrocardiograms and echocardiograms were used for follow-up evaluation of the treatment within 1 day, 1 month and 3–6 months after successful closure. Results: 20 of the 29 patients had successful occlusion (group 1), and 9 patients failed (named group 2). In group 1, in which occlusion was successful, mean (SD) pulmonary arterial pressures decreased markedly after trial occlusion: 78 (19.3) mm Hg (range 50–125 mm Hg) before occlusion and 41 (13.8) mm Hg (range 23–77 mm Hg) after occlusion. Systemic arterial oxygen saturation was found to be >90% in 19 patients and <90% in the remaining patient before inhalation of oxygen, and >95% during inhalation of oxygen or after occlusion in all 20 patients. In group 2, the occlusion was not successful, because in two patients the device was not available; another two patients showed worsening of symptoms. The other five patients showed increased pulmonary arterial pressures after trial closure; their mean (SD) pulmonary arterial pressures increased by 10.3 (6) mm Hg (4–16 mm Hg) after trial occlusion, and systemic arterial oxygen saturation was 85.5% (2.6%) (range 82.6–88%) before inhalation of oxygen and 94.7% (1.7%) (range 90.7–99.1%) during inhalation of oxygen. In group 1, the dimensions of the left atrium, left ventricle and pulmonary artery increased considerably in 3–6-months of follow-up compared with those of preocclusion. Conclusions: Transcatheter closure is an effective treatment for adults with PDA associated with reversible severe pulmonary arterial hypertension. Further research is needed for the evaluation of long-term results.